2020
DOI: 10.1016/j.aquaculture.2020.735433
|View full text |Cite
|
Sign up to set email alerts
|

Species composition in the Molobicus hybrid tilapia strain

Abstract: Novel SNP markers revealed species contribution within a hybrid tilapia line (Molobicus) undergoing selection for growth performance in brackish water.• The backcross base population, developed from feral Oreochromis mossambicus and GIFT, matched the predicted 3:1 ratio for O. mossambicus and O. niloticus respectively.• The selected lines showed a significant increase in O. niloticus-specific alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“… Genetic origins of Oreochromis niloticus in sampled core populations: 1 Bartie et al ( 2020 ), 2 Eknath et al ( 1993 ), 3 Ordoñez et al ( 2014 ), 4 Ponzoni et al ( 2010 ), 5 Pullin ( 1988 ), 6 Rezk et al ( 2002 ), 7 Rodriguez ( 2006 ), 8 Scott et al ( 1989 ), 9 Tayamen et al ( 2002 ), 10 Tayamen et al ( 2004 ), 11 Tayamen ( 2004 ), 12 Bureau of Fisheries and Aquatic Resources National Integrated Fisheries Technology Development Center, 13 Center de Cooperation Internationale en Recherche Agronomique pour le Development, 14 Bureau of Fisheries and Aquatic Resources National Freshwater Fisheries Technology Center, 15 Freshwater Aquaculture Center Central Luzon State University, 16 University of the Philippines Visayas, 17 International Development Research Center. …”
Section: Methodsmentioning
confidence: 99%
“… Genetic origins of Oreochromis niloticus in sampled core populations: 1 Bartie et al ( 2020 ), 2 Eknath et al ( 1993 ), 3 Ordoñez et al ( 2014 ), 4 Ponzoni et al ( 2010 ), 5 Pullin ( 1988 ), 6 Rezk et al ( 2002 ), 7 Rodriguez ( 2006 ), 8 Scott et al ( 1989 ), 9 Tayamen et al ( 2002 ), 10 Tayamen et al ( 2004 ), 11 Tayamen ( 2004 ), 12 Bureau of Fisheries and Aquatic Resources National Integrated Fisheries Technology Development Center, 13 Center de Cooperation Internationale en Recherche Agronomique pour le Development, 14 Bureau of Fisheries and Aquatic Resources National Freshwater Fisheries Technology Center, 15 Freshwater Aquaculture Center Central Luzon State University, 16 University of the Philippines Visayas, 17 International Development Research Center. …”
Section: Methodsmentioning
confidence: 99%
“…These results showed that the pipeline is capable of confidently recognising the ancestry of admixed individuals, as the hybrids analysed were indeed descendants of O. niloticus . Fish from the GIFT breeding programme have already been shown as having a small contribution from O. mossambisus genome and O. aureus 28 30 . The actual extent depends on the methodology used, but it ranges from 1 to 7% for O. mossambisus and 0.5% to 3% for O. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Purified DNA was extracted by a modified salt precipitation method 30 . Small pieces of fin tissue were digested in 300 μL SSTNE lysis solution (0.3 M NaCl, 50 mM Tris base, 0.2 mM EDTA pH 8.0, 0.2 mM EGTA, 0.5 mM spermidine, 0.25 mM spermine and 0.1% SDS) containing 1.5 μL Proteinase K (10 mg/mL) at 55 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…This process was repeated to give three independent transposon insertion mutant libraries. Finally, duplicate 0.5-mL aliquots of each library were cultured in 5 mL TSB 15 + KAN 250 + STR 100 (22℃, 150 rpm, 3 h) before genomic DNA from 3 mL of each of the six cultures was extracted according to Bartie et al ( 2020 ).…”
Section: Methodsmentioning
confidence: 99%